2014
DOI: 10.1177/0731948714526998
|View full text |Cite
|
Sign up to set email alerts
|

Impact of The Personal Strengths Program on Self-Determination Levels of College Students With LD and/or ADHD

Abstract: This study investigates the impact of The Personal Strengths Program (PSP) on seven college students with learning disabilities and/or attention deficit hyperactivity disorder (LD/ADHD) using a multiple baseline design. Students with LD/ADHD experience increased challenges in school settings and decreased post-secondary outcomes when compared with their peers without disabilities. Research has indicated that students who are able to transition into post-secondary settings successfully often have higher levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…Other researchers have suggested that specific knowledge and skills comprise self‐advocacy, such as self‐determination and the abilities to make independent decisions and express one's needs (Phillips, ). Self‐determination has been further defined as a dispositional characteristic indicated by behaviors that are based on autonomy, self‐regulation, self‐realization, and psychological empowerment (Farmer, Allsopp, & Ferron, ). Therefore, self‐advocacy might be thought of as the expression of one's needs made possible by knowledge of self, the ability to make independent decisions, and an empowered psychological state.…”
Section: Self‐advocacy Skills and Students With Learning Disabilitiesmentioning
confidence: 99%
“…Other researchers have suggested that specific knowledge and skills comprise self‐advocacy, such as self‐determination and the abilities to make independent decisions and express one's needs (Phillips, ). Self‐determination has been further defined as a dispositional characteristic indicated by behaviors that are based on autonomy, self‐regulation, self‐realization, and psychological empowerment (Farmer, Allsopp, & Ferron, ). Therefore, self‐advocacy might be thought of as the expression of one's needs made possible by knowledge of self, the ability to make independent decisions, and an empowered psychological state.…”
Section: Self‐advocacy Skills and Students With Learning Disabilitiesmentioning
confidence: 99%
“…Acquiring coping skills such as developing strategies for self-regulation and organization are skills required in the postsecondary graduate environment, and for those students who face complex embodiments such as learning disabilities, mental health disorders, and outside responsibilities, this can often result in low academic performance due to an inability to adapt these skills to the educational environment. (Farmer, Allsopp, & Ferron, 2015).…”
Section: Coping Strategies and The Use Of Learned Creativity In Academentioning
confidence: 99%
“…According to the Institute of Education Sciences [1], those with a learning disability (LD) and/or attention deficit hyperactivity disorder (ADHD) collectively represent almost half of all students with disabilities (SDs) attending two-and four-year postsecondary institutions. Their attendance rate (60.9%) is lower than those of typically developing students (62.1%) [2], as is their college completion rate (37.5% and 51.2%, respectively) [3]. While many reasons have been offered for this discrepancy, these figures reflect the difficulty that SDs experience in adjusting to postsecondary school [4], as they are often not ready for academic college programs [5], showing difficulties in the areas of organization, attention, cognition, and information processing [6].…”
Section: Introductionmentioning
confidence: 99%